Clinical attendance rates and associated factors after discharge of patients treated in a child psychiatry clinic (Annals of Medical Research, 2021)
Aim: Continual attendance at clinical follow-ups of children and adolescents after inpatient psychiatric treatment is an important problem affecting morbidity and mortality. In this study we aimed to research the follow-up attendance rates after hospital discharge and influencing factors in a child and adolescent psychiatric inpatient clinic.Material and Methods: Patient data between 2013 and 2016 were retrospectively investigated and cases with at least 3 months of history after discharge were included in the study. After discharge, cases who attended the following first 2 consecutive clinic appointments were accepted as attending follow-up. Variables related to sociodemographic characteristics, psychiatric diagnosis, applied treatment, kind of admission and discharge, duration of stay, applied psychometric scale scores were also recorded. Results: Two-hundred and fourty-one cases (65.7%) attended the first two consecutive appointments, while 126 cases (34.3%) did not attend a total of 367 cases. Low socioeconomic level and alcohol use were found to be associated independently with lower attendance rates while pharmacotherapy, admission from outpatient clinic and those with first-degree relatives who had mental disorders associated independently with higher attendance rates.Conclusion: Regular and consistent follow-up after discharge from children and adolescents may be an important indicator of compliance with treatment. Studies have reported that repeated psychiatric admissions to hospital are lower among patients who are compliant with treatment compared to those who do not comply. We believe our study will contribute to the literature on understanding the attendance rates and effective factors for clinical check-ups after discharge.